Part IV – April 1968 - Communications - Effect of Residual Gas Composition on the Fatigue Behavior of Aluminum - M. A. Wright; M. J. Hordon (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
ReCENT work has indicated that the substantial decrease in the rate of fatigue crack propagation for aluminum observed below a critical vacuum level can be attributed to the depletion of oxygen or water vapor from the vicinity of the fatigue crack opening.' At reduced gas pressures, generally below 10-2 Torr with fatigue strain amplitudes in the range *1 to 2 x 10-3 and cyclic loading rates of 25 to 50 cps, estimated rates of oxide or hydroxide monolayer adsorption on newly formed crack surfaces can fall behind the actual rate of crack extension. Changes in the critical pressure required for the transition in fatigue behavior with changes in temperature, strain amplitude, and cyclic frequency can be interpreted from variations in the adsorption and crack growth rates.'" Although the adsorption model generally appears to explain the enhanced fatigue resistance of reactive metals in vacuum, the specific adsorbing gas species and nature of the adsorption mechanism are uncertain. In addition to the direct dissociation and adsorption of O2 on the metal surfaces,3 the dissociation of H20 and subsequent adsorption of H ions have been advanced for aluminum alloys.4 The present note describes some measurements of the fatigue behavior of 1100 aluminum in reduced partial pressures of specific gases including O2, H2O, and H2 in order to provide additional experimental data. Cantilever-type specimens of 1100-H14 aluminum were fatigued in cyclic reverse bending at constant strain amplitude using a multispecimen vacuum apparatus and procedure described previously.' After initial vacuum evacuation to 1 x 10-7 Torr, the appropriate gas species was bled into the system through a calibrated leak valve. The input rate was adjusted to maintain the desired pressure level under continuous evacuation, thus minimizing possible changes in gas composition during testing. High-purity input gases including 99.9 pct O2, 99.999 pct H 2, and water vapor from triply distilled H 2 O were used to provide residual pressures. Trace amounts of contaminant species were limited by passing the Oz and H 2 input gases through liquid-nitrogen-cooled copper coils prior to entry to the test chamber. Care was taken to repeatedly flush the gas lines and valves before testing to minimize the effect of adsorbed contaminants. Residual gas pressures in the range 10-6 to 5 x x3 Torr were monitored by an NRC ionization gage corrected for each gas species. In the higher-pressure range, 5 x 1CT3 to 5 x 10' Torr, an NRC alphatron gage was used. In operation, eight simultaneous fatigue tests were conducted at a constant strain amplitude of *1.2 x 10 at cyclic bending rates of 25 and 50 cps to give an average fatigue life of 6.5x 105 cycles-to-fracture at standard atmosphere and 3.3 x 106 cycles in 1 x 10"7 Torr vacuum. Representative results for the effect of residual O2, H2O, and H2 contents on the fatigue life are shown in Fig. 1 for tests performed at 50 cps. It is apparent that the presence of either O2 or H2O gas in the system at partial pressures greater than 10"3 Torr was noticeably detrimental to the fatigue life. In contrast, the enhanced fatigue resistance typical of high-vacuum environments was retained with pure H 2 through the pressure range up to 1 Torr. For partial pressures of H2 gas above 1 Torr, the fracture life noticeably decreased. The critical Hz